Synthesis of Symmetrical Monocarbonyl Analogs of Curcumin Containing a 2-Bromobenzylidene Moiety and Spectrophotometric Assessment of Their Reactivity with 2-(Dimethylamino)ethanthiol - Zlatko Lozanovski; Ivana Todorovska; Katerina Dragarska; Jane Bogdanov (Chemistry Proceedings)
The cross-conjugated dienones containing the 1,5-diaryl-3-oxo-1,4-pentadienyl pharmacophore have diverse biological activities. These sometimes-called monocarbonyl analogs of curcumin (MACs) have especially pronounced biological activity when containing an electron-withdrawing group at the ortho-position of the benzene ring. Their biological activity most likely stems from a selective Michael reaction with thiols. It has been reported in the literature that certain MACs (in particular, EF24) react as electrophiles with glutathione and form bis adducts in vitro. Five MACs were prepared ((2E,5E)-2,5-bis(2-bromobenzylidene)cyclopentanone, (2BrCP), (2E,6E)-2,6-bis(2-bromobenzylidene)cyclohexanone (2BrCX, B2BrBC), (2E,6E)-2,6-bis(2-bromobenzylidene)- 4-tert-butyl-cyclohexanone (4tB2BrCX), (3E,5E)-3,5-bis(2-bromobenzylidene)-4-piperidone, (2Br4PIP) and (3E,5E)-3,5-bis(2-fluorobenzylidene)-4-piperidone, EF24), purified and characterized by spectroscopic means. The relative reactivity of these MACs towards 2-(dimethylamino)ethanethiol was assessed via a previously developed UV-Vis spectroscopic method and compared to EF24, which reacts readily in solution with thiols such as glutathione and cysteamine. All of the bis(2-bromobenzylidene) MACs react slower with 2-(dimethylamino)ethanethiol in 80:20 (v/v) acetonitrile/water compared to EF24. The relative reactivity of the analogs with 2-(dimethylamino)ethanethiol followed the order EF24 > 2Br4PIP > 2BrCX > 2BrCP > 4tB2BrCX.